On the road to sustainability: Applying an extended Theory of Planned Behaviour model to energy-saving transportation practices - Anda-Bianca Ciocîrlan; Richard Rowe (PLoS ONE, 2025)
Mitigating climate change demands urgent action, particularly in reducing CO2 emissions, a major contributor to global warming. Individual behavioural changes in transportation patterns are needed to lower environmental impact. To design interventions that can target these behaviours, it is essential to understand the beliefs that underlie them. This study uses an extended Theory of Planned Behaviour model to identify the beliefs underlying sustainable transportation practices. Five behaviours were included: (i) general sustainable transportation, (ii) public transportation, (iii) walking and cycling, (iv) reducing car use, and (v) reducing flights. A three step-approach was employed. First, beliefs underlying the Theory of Planned Behaviour variables were elicited using qualitative methodology. The most commonly stated beliefs were included in the second phase; a questionnaire study that measured beliefs, attitudes, subjective norm, perceived behavioural control, habit, moral norms, and intention. Lastly, a one-week follow-up measured behaviour. Behavioural beliefs strongly predicted attitudes, habit beliefs predicted habit, and moral norm beliefs predict moral norm across all five behaviours. Regression models showed that the extended Theory of Planned Behaviour model had a better predictive capacity than the standard model. The strongest predictors were habit and moral norm. Intention significantly predicted behaviour but only explained a low proportion of variance. Interventions aiming to promote sustainable transportation practices should particularly focus on influencing individuals’ habits and moral norms, as these factors impacted most behaviours studied.